Pemberdayaan Masyarakat Lokal melalui Produksi dan Inovasi Gipang untuk Memperkuat Perekonomian Daerah: Empowering Local Communities through Gipang Production and Innovation to Strengthen the Regional Economy - Ratna Ekawati; Shanti Kirana Anggraeni; Muhammad Adha Ilhami; Tamara Arip Hidayah; Findi Choerun Annisa (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2026)
Cilegon City, widely recognized as an industrial hub, faces challenges in promoting more inclusive local economic growth, making the development of micro, small, and medium enterprises (MSMEs) based on traditional products increasingly important. One of the local potentials is gipang, a traditional snack made from glutinous rice or cassava, which carries both cultural value and economic opportunities. This study aims to design and implement a community empowerment model through gipang product innovation to enhance MSME production capacity, quality, and competitiveness. The research method involved identifying key problems, collecting primary data through surveys and interviews, conducting both qualitative and quantitative analyses, and designing an empowerment model that included hygienic production training, product diversification, modern packaging design, digital marketing, and limited-scale pilot testing. The findings reveal a positive trend: production increased from 1,200 kg in 2020 to 2,600 kg in 2024, while sales rose from IDR 180 million to IDR 440 million. MSMEs involved in the intervention recorded a 20–30% increase in turnover within the first six months and began creating new employment opportunities. These results demonstrate that gipang-based empowerment not only raises household income and community skills but also strengthens Cilegon’s cultural identity. Therefore, developing gipang MSMEs can serve as a relevant strategy for economic diversification amid the dominance of heavy industry, and is recommended to be sustained through institutional strengthening, continuous innovation, digitalization, and integration with the tourism sector.